Mu`alajah al-Riddah fi `Asr al-`Aulamah Dirasah Fiqhiyyah - Ijtima`iyyah - al-Sifi, Hisam (Jurnal Fiqh, 2009)
This study is to explain measures that should be taken in order to prevent the spread of apostasy in the Muslims society. Instead of focusing on punishment measures as discussed in fiqh, this study is devoted to discuss preventive measures from theological, sociological, educational and economical aspects. The study finds that the causes of apostasy, apart from the missionary movement, can be traced to many factors including psychological crisis, educational failure, westernization upbringing and environment and also poor economic condition. To facilitate the understanding of the issues in hand this study has been divided into three parts, namely, theological, educational, which includes da’wah, and socio-economical aspects.